Erb-duchenne palsy (case report) - Senatorova, A.; Khodun I. (My University, 2018)
The frequency of damage to the brachial plexus is 0.5–2 per 1000 live births. Most of them (about 90 % cases) are Erb-Duchesnne palsy. Birth trauma of the brachial plexus occurs mainly in in full-term newborns. Correct diagnosis of Erb-Duchesnne palsy allows to avoid long-term complications as late treatment leads to disability. The article presents a clinical observation of Erb-Duchesnne palsy in a newborn patient, who was diagnosed on the first day of life. Conservative therapy was an effective strategy of baby's recovery
Keywords: Erb-Duchenne palsy; birth injury